2006
DOI: 10.1016/j.coldregions.2005.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Measuring thermal conductivity in freezing and thawing soil using the soil temperature response to heating

Abstract: The thermal conductivity of the thin seasonally freezing and thawing soil layer in permafrost landscapes exerts considerable control over the sensitivity of the permafrost to energy and mass exchanges at the surface. At the same time, the thermal conductivity is sensitive to the state of the soil, varying, for example, by up to two orders of magnitude with varying water contents. In situ measurement techniques perturb the soil thermally and are affected by changes in soil composition, for example through varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 28 publications
2
56
1
Order By: Relevance
“…During the measurements, the heating needle releases a short heat pulse and the detecting needles measures the temperature T (°C) changes some distance from the heater. Heat propagation from the line source can be represented by the heat conduction equation in radial coordinates [ Patankar , 1980; Overduin et al , 2006]: where r is the radial distance from the center of the heating needle, b is the radius of the heating needle, t is time after heating start (s), and C and λ are soil volumetric heat capacity (J m −3 °C −1 ) and thermal conductivity (J °C −1 m −1 s −1 ), respectively. A constant heat source q′ (J m −1 s −1 ) is applied at r = b during the heat pulse duration t 0 (s) as a flux boundary to in order to solve the temperature at time t and distance r .…”
Section: Theoretical Models Of Heat Pulse Probesmentioning
confidence: 99%
“…During the measurements, the heating needle releases a short heat pulse and the detecting needles measures the temperature T (°C) changes some distance from the heater. Heat propagation from the line source can be represented by the heat conduction equation in radial coordinates [ Patankar , 1980; Overduin et al , 2006]: where r is the radial distance from the center of the heating needle, b is the radius of the heating needle, t is time after heating start (s), and C and λ are soil volumetric heat capacity (J m −3 °C −1 ) and thermal conductivity (J °C −1 m −1 s −1 ), respectively. A constant heat source q′ (J m −1 s −1 ) is applied at r = b during the heat pulse duration t 0 (s) as a flux boundary to in order to solve the temperature at time t and distance r .…”
Section: Theoretical Models Of Heat Pulse Probesmentioning
confidence: 99%
“…Approximately 35% of the earth's surface is subject to seasonal freezing and thawing, with 26% estimated to be underlain with permafrost [ Williams and Smith , 1989]. Because the thermal and hydraulic properties of frozen soils are distinct from those of the same soil in the unfrozen state [ Lachenbruch et al , 1982; Farouki , 1986; McCauley et al , 2002; Quinton et al , 2005; Overduin et al , 2006], ground thawing and freezing processes strongly influence the surface energy balance and hydrological processes [ Woo , 1986; Williams and Smith , 1989]. The latent energy consumed (released) during thawing (freezing), along with changes in soil thermal properties, greatly alters the surface and subsurface energy partitioning patterns during the unfrozen, frozen and transition periods in permafrost soil [ Boike et al , 1988; Gu et al , 2005; Quinton et al , 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have prescribed surface forcing [e.g., Jumikis , 1977; Goodrich , 1978, 1982b; Lunardini , 1981; Riseborough , 2004], or prescribed soil moisture and thermal properties [e.g., Goodrich , 1978, 1982b; Romanovsky et al , 1997; Hinzman et al , 1998; Li and Koike , 2003; Ling and Zhang , 2004; Woo et al , 2004]. For example, in the validation of a modified Stefan's algorithm, a 5% unfrozen water content was used for six field sites ranged from polar desert to agricultural land [ Woo et al , 2004], while observed values ranged from 0% in coarse‐grained mineral soil to more than 20% in certain organic or clay soils [ Anderson and Tice , 1972; Nakano and Brown , 1972; Romanovsky and Osterkamp , 2000; Quinton et al , 2005; Overduin et al , 2006]. Most existing evaluation/validation studies of GTFD simulations only included single algorithm [e.g., Goodrich , 1978; Fox , 1992; Hinkel and Nicholas , 1995; Hinzman et al , 1998; Cherkauer and Lettenmaier , 1999; Quinton and Gray , 2001; Zhang et al , 2003; Woo et al , 2004; Hayashi et al , 2007], and only a few compared different algorithms [e.g., Romanovsky et al , 1997; Luo et al , 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Their numerical study showed that the SHB method could determine ice content as a function of depth and time at the centimeter scale if accurate thermal properties were obtained. However, the feasibility of the SHB method for soil freezing and thawing is unknown because of the difficulties in measuring soil thermal properties in partially frozen soils (Putkonen, 2003; Overduin et al, 2006; Ochsner and Baker, 2008; Watanabe et al, 2010). Further evaluation of the SHB method for partially frozen soil is warranted including, in particular, evaluation of the required HP measurement inputs under these challenging conditions.…”
mentioning
confidence: 99%